(3JMaI GdNdjd aj CNHGQ eUQ hGdfjds - (3eMeO Hf eMeO GdZRGdj, CHh MGeOs
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd GdHdGO GdeUQjI Ydi cKjQ ef GdHdOGf s
(3fSNI HOhf JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B82 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdEScfOQjI (B(756 (3O(B) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdJGQjNs